The Black Towns - Crockett, Norman L. (University Press of Kansas, 1979)
From Appomattox to World War I, Blacks continued their quest for a secure position in the American system. The problem was how to be both black and American-how to find acceptance, or even toleration, in a society in which the boundaries of normative behavior, the values, and the very definition of what it meant to be an American were determined and enforced by whites. A few black leaders proposed selfsegregation inside the United States within the protective confines of an allBlack community as one possible solution. The Blacktown idea reached its peak in the fifty years after the Civil War; at least sixty Black communities were settled between 1865 and 1915.Norman L. Crockett has focused on the formation, growth and failure of five such communities. The towns and the date of their settlement are: Nicodemus, Kansas (1879), established at the time of the Black exodus from the South; Mound Bayou, Mississippi (1897), perhaps the most prominent Black town because of its close ties to Booker T. Washington and Tuskegee Institute: Langston, Oklahoma (1891), visualized by one of its promoters as the nucleus for the creation of an allBlack state in the West; and Clearview (1903) and Boley (1904), in Oklahoma, twin communities in the Creek Nation which offer the opportunity observe certain aspects of IndianBlack relations in this area.The role of Blacks in town promotion and settlement has long been a neglected area in western and urban history, Crockett looks at patterns of settlement and leadership, government, politics, economics, and the problems of isolation versus interaction with the white communities. He also describes family life, social life, and class structure within the black towns.Crockett looks closely at the rhetoric and behavior of blacks inside the limits of their own community-isolated from the domination of whites and freed from the daily reinforcement of their subordinate rank in the larger society. He finds that, long before "Black is beautiful" entered the American vernacular, Blacktown residents exhibited a strong sense of race price. The reader observes in microcosm Black attitudes about many aspects of American life as Crockett ties the Blacktown experience to the larger question of race relations at the turn of the century.This volume also explains the failure of the Blacktown dream. Crockett cites discrimination, lack of capital, and the many forces at work in the local, regional, and national economies. He shows how the racial and townbuilding experiment met its demise as the residents of allBlack communities became both economically and psychologically trapped.This study adds valuable new material to the literature on black history, and makes a significant contribution to American social and urban history, community studies, and the regional history of Kansas, Oklahoma, and Mississippi.